Screening for Cystic Fibrosis Related Complications in the Context of a Pandemic and Altered Models of Care - Michael Doumit; Roxanne Strachan; Raynuka Lazarus; Peter Middleton; Ruth Dentice; Jessica Marouvo; Laura Jeffrey; Hiran Selvadurai; Sheila Sivam; Verity Pacey; Adam Jaffe; Kelly Gray (Health Services Insights, 2023)
Background: Standard of care recommend that patients with cystic fibrosis (CF) require screening investigations to assess for complications. Changing models of care due to the COVID19 pandemic may have impacted completion of recommended screening. Objective: To compare the frequency of screening investigations completed in people with CF before and after the onset of the COVID19 pandemic. Methods: Medical records were reviewed at 4 CF-specialist centers to identify screening investigations completed in the 12-months before and after pandemic onset. Results: Records of 625 patients were reviewed. Prior to pandemic onset, there was between center variability in completion of screening investigations. There was greatest baseline variation between centers in performing oral glucose tolerance test (OGTT); range 38%-69%, exercise tests; 3%-51% and sputum screening for non-tuberculous mycobacteria; 53%-81%. Following pandemic onset, blood tests, and sputum cultures were maintained at the highest rates. Exercise testing, CXR and OGTT exhibited the greatest declines, with reductions at individual centers ranging between 10%-24%, 22%-43%, and 20%-26%, respectively. Return to in-person visits following pandemic onset was variable, ranging from 16% to 74% between centers. Conclusion: Completion of screening investigations varies between CF centers and changes in models of care, such as increased virtual care in response to COVID19 pandemic was associated with reduction in completion of investigations. Centers would benefit from auditing their adherence to standards of care, particularly considering recent changes in care delivery.